Taming the star runner - Hinton, S. E. (New York, N.Y. : Delacorte Press, 1988)
Sent to live with his uncle after a violent confrontation with his stepfather, sixteen-year-old Travis, an aspiring writer, finds life in a small Oklahoma town confining until he meets an eighteen-year-old horse trainer named Casey.
Booklist.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
5.6
5.6
7-10.
Keywords: Authorship -- Fiction; Horses -- Fiction; Authorship -- Fiction; Horses -- Fiction